Recovery after patella fracture - case report - Chobot, Barbara; Dworak, Kinga; Wachowska, Marta; Chmielowiec, Julia; Chludek, Aleksandra; Dańda, Karol; Czyżewicz, Zuzanna; Trędota, Natalia; Posid, Dominika; Lewczuk, Michał (Quality in Sport, 2026)
Introduction: The aim of this study is to present the rehabilitation process of a patient after a comminuted patellar fracture, with particular emphasis on the physiotherapeutic methods applied and their impact on the recovery of knee joint function. The study is a case report and includes an analysis of successive stages of rehabilitation, including pain and edema reduction, restoration of range of motion, muscle strengthening, and functional re-education. The results obtained indicate that an individually tailored physiotherapy program plays a key role in the treatment process and enables the patient’s gradual return to sports activity. Materials and methods: Comprehensive review of the literature available on PubMed, Google Scholar, Polona, online collections of journals from medical universities, database by searching the keywords “patella fracture”, “rehabilitation after fracture”, “patella injury”. Conclusion: This case demonstrates the complexity of rehabilitation. When carried out in the manner described below, it ensures a rapid return of the patient to pre-injury functionality, which is the primary goal in patient care. By combining different physiotherapeutic methods, we can achieve satisfactory results in restoring functionality quickly. Collaboration among various specialists is crucial in working towards this shared goal.